Comparisons of College Students’ Enjoyment in Physical Activity & Exergames - Yoonsin Oh; Matthew S. Wiggins; Mary Beth Leibham (European Scientific Journal, ESJ, 2016)
The purpose of this study was to compare college students’ enjoyment levels in three domains of activity (traditional physical activities, exergames, and non-exergames). Volunteers (n = 141) from a Midwestern university completed an online survey composed of a modified version of the Physical Activity Enjoyment Scale (PACES). Significant differences were detected across the three domains regarding level of enjoyment, F(2, 232) = 32.49, p < .001, with the highest enjoyment levels reported in the traditional physical activity domain. Additional results revealed that Wii Sports (49%) and Just Dance (29%) had the highest percentage of use with exergamers, while non-exergame participants reported playing video games such as Pokémon, Zelda, Mario Kart, Madden (59%), and Clash of Clans (25%). These results suggest that traditional physical activities and exergaming activities are psychologically enjoyable pursuits for college-aged individuals that can help increase their physical health and quality of life.